2022
DOI: 10.20517/jeea.2022.25
|View full text |Cite
|
Sign up to set email alerts
|

First insights into the occurrence of pesticide residues in edible insects from sub-Saharan African countries

Abstract: Pesticide use is a common practice worldwide, especially in Sub-Saharan African (SSA) countries, where ongoing agriculture intensification and the need for disease vector control make it essential. The population can thus be exposed to variable amounts of pesticides through the diet. Edible insects are a highly regarded food source in SSA. However, they are still mostly harvested from the wild, where chemical applications are not necessarily controlled, representing a major cause of concern for consumers. We i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 24 publications
(36 reference statements)
0
3
0
Order By: Relevance
“…Indeed, edible insects are mainly caught in cropping areas, where they are also considered by some farmers as crop pests and killed with pesticides. In fact, some studies showed that edible insects collected in crop fields have a high quantity of pesticide residues on and recommended their farm rearing according to appropriate regulations to ensure safety [43,44]. It would therefore be interesting to assess the level of pesticide residues contained in the main edible insects consumed in Benin.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, edible insects are mainly caught in cropping areas, where they are also considered by some farmers as crop pests and killed with pesticides. In fact, some studies showed that edible insects collected in crop fields have a high quantity of pesticide residues on and recommended their farm rearing according to appropriate regulations to ensure safety [43,44]. It would therefore be interesting to assess the level of pesticide residues contained in the main edible insects consumed in Benin.…”
Section: Discussionmentioning
confidence: 99%
“…Detecting pesticides within insects themselves serves multiple purposes, including verifying a pesticide's effectiveness against both target and non-target insects, acting as a bioindicator to ascertain the actual amount of pesticide reaching insects, and shedding light on how different insect groups respond to pesticide applications in crops. While these assessments are more commonly conducted on foods intended for human consumption due to methodological considerations, it is noteworthy to emphasize that there exists a specific number of studies directly measuring the detection of pesticide levels in insects [48]. Therefore, this approach presents several challenges, including determining the detectable concentration of pesticides within an insect's body and establishing the required sample size for effective detection.…”
Section: Discussionmentioning
confidence: 99%
“…As such, even minimal transfer rates from substrate to insect biomass could lead to noncompliance of the produced larval biomass when used in feed or food. Varying levels of insecticides in collected or reared edible insects have recently been reported in, for instance, several African countries (Labu et al, 2022;Poma et al, 2022), Thailand (Kanthawongwan et al, 2019), Belgium (Poma et al, 2017), and Canada (Kolakowski et al, 2021)suggesting that the presence of insecticide residues in insect products marketed for human consumption are a cause for some concern. Therefore, these results warranted additional research on the effects of insecticide residues on BSFL.…”
Section: Introductionmentioning
confidence: 99%